Anti-inflammatory effects of chlorogenic acid from Taraxacum officinale on LTA-stimulated bovine mammary epithelial cells via the TLR2/NF-κB pathway. - Ping Xu; Xiaobo Xu; Hanna Fotina; Tetiana Fotina (PLoS ONE, 2023)
Mastitis is an inflammatory disease caused by microbial infection. Chlorogenic acid (CGA), one of the major phenolic acids in Taraxacum officinale, has natural antioxidant and anti-inflammatory properties in various cell types; however, the effects of CGA on Lipoteichoic acid (LTA)-induced bovine mammary epithelial cells (BMECs) have not been investigated. In this study, the CGA content in T. officinale was determined by High-performance liquid chromatography (HPLC). BMECs were infected with LTA to induce the mastitis model. Different concentrations of CGA were administered after establishing the LTA infection. The results showed that the T. officinale contained CGA 1.36 mg/g. CGA significantly reduced the pro-inflammatory gene and protein expression of TNF-α, IL-6, and IL-1β. In addition, CGA downregulated the NO, TLR2, and NF-κB signaling pathways in LTA-infected bovine mammary epithelial cells. Our results indicate that CGA reduced the expression of TNF-α, IL-6, IL-1β, and TLR2 by inhibiting the phosphorylation of proteins in the NF-κB signaling pathways in a dose-dependent manner. This finding suggests that CGA may be a potential agent for the treatment of mastitis in dairy cows.